Comparative Analysis of Biochemical and Cellular Profiles in Acute Gastroenteritis Patients with Comorbidities: A Retrospective Study in a Resource-Limited Setting - Kumari, Hema; Kumar, Gaurav (South Eastern European Journal of Public Health, 2025)
This study aims to compare critical laboratory parameters in patients diagnosed with acute gastroenteritis (AGE) with various comorbidities, highlighting trends and abnormalities in biochemistry and cellular profiles. Conducted at Yatharth Hospital, Greater Noida, India, this retrospective study includes 284 patients admitted between March 2018 and May 2022. Key parameters such as total leukocyte count (TLC), sodium, and liver enzymes (SGPT/SGOT) were evaluated and compared across different age groups and comorbidities, including dehydration, acute febrile illness, diabetes, and hypertension. Significant deviations were identified in patients with comorbidities, particularly in sodium levels and liver enzyme markers, which may aid in early detection and management. This study's findings provide valuable insights for resource-limited settings, contributing to more effective treatment strategies and resource allocation, especially in low- and middle-income countries (LMICs), where AGE remains a major health concern.